Application of propionate-producing bacterial consortium in ruminal methanogenesis inhibited environment with bromoethanesulfonate as a methanogen direct inhibitor - Jeong, Jongsik; Yu, Chaemin; Kang, Ryukseok; Kim, Myunghoo; Park, Tansol (Frontiers in Veterinary Science, 2024)
Methane production in ruminants is primarily due to the conversion of metabolic hydrogen (H2), produced during anaerobic microbial fermentation, into methane by ruminal methanogens. While this process plays a crucial role in efficiently disposes of H2, it also contributes to environmental pollution and eliminating methane production in the rumen has proven to be challenging. This study investigates the use of probiotics, specifically propionate-producing bacteria, to redirect accumulated H2 in a methane-mitigated environment. For this objective, we supplemented experimental groups with Lactiplantibacillus plantarum and Megasphaera elsdenii for the reinforced acrylate pathway (RA) and Selenomonas ruminantium and Acidipropionibacterium thoenii for the reinforced succinate pathway (RS), as well as a consortium of all four strains (CB), with the total microbial concentration at 1.0 × 1010 cells/mL. To create a methane-mitigated environment, 2-bromoethanesulfonate (BES) was added to all experimental groups at a dose of 15 mg/0.5 g of feed. BES reduced methane production by 85% in vitro, and the addition of propionate-producing bacteria with BES further decreased methane emission by up to 94% compared with the control (CON) group. Although BES did not affect the alpha diversity of the ruminal bacteriome, it reduced total volatile fatty acid production and altered beta diversity of ruminal bacteriota, indicating microbial metabolic adaptations to H2 accumulation. Despite using different bacterial strains targeting divergent metabolic pathways (RA and RS), a decrease in the dominance of the [Eubacterium] ruminantium group suggesting that both approaches may have a similar modulatory effect. An increase in the relative abundance of Succiniclasticum in the CB group suggests that propionate metabolism is enhanced by the addition of a propionate-producing bacterial consortium. These findings recommend using a consortium of propionate-producing bacteria to manage H2 accumulation by altering the rumen bacteriome, thus mitigating the negative effects of methane reduction strategies.